Thai pregnant women knowledge and attitudes about maternal serum screening for Down's syndrome - Manatsawee Manopunya; Chanane Wanapirak (The Royal Thai College of Obstetricians and Gynaecologists, 2008)
ObjectiveTo study the knowledge and the attitude about maternal serum screening for Down's syndrome in Thai pregnant women. Study design Cross-sectional descriptive study. SettingDepartment of Obstetrics and Gynecology, Faculty of Medicine, Chiang Mai University. Subjects242 pregnant women who were 18 years or older, with a singleton live fetus and gestational age of 10 through 21 weeks. All of them attended antenatal clinics between 1 January and 30 April 2007. MethodsAn experimental maternal serum screening program offered to pregnant women, together with a series of questionnaires to be completed before and after the counseling. Main outcome measureWomen's knowledge and understanding of prenatal screening test; attitude towards screening offer; perceive freedom of choice and satisfaction with information given. ResultsNinety-seven percent of women accepted the offer of maternal serum screening. Most of women had previous knowledge of Down's syndrome, whereas there are limitations in knowledge of maternal serum screening and diagnostic tests. Almost (80%) of them considered the information given before screening was clear and sufficient for decision making. Fifty-three percent of women felt worried to some extent after being given the information. The majority of women showed a positive attitude towards the offer of maternal serum screening. Eighty-seven percent of women agree that information on Down's syndrome screening should be extended to all pregnant women. ConclusionMaternal serum screening was well accepted after the counseling, although the pregnant women had limited understanding. Majority of women were satisfied with this offering. However effective and clear communication are needed.